"Yes, sir": Leadership and blind obedience in hierarchal organisations. Issue 1 (6th December 2017) - Drummond-Smith, Ian
Abstract : Purpose: The purpose of this paper is to explore human issues within subordinate and leader interaction and guide police leaders in how they can achieve success. Although focussed on uniformed services, leaders from all areas will find the arguments presented here useful. Design/methodology/approach: The paper draws on a number of catastrophic case studies, including the collision of two war ships, two Jumbo Jets, the defeat of the Spanish Armarda and the failure of Hitler's military to respond effectively to the D-Day landings. It will examine work by Rittel and Webber (1973) and Grint (2005), who propose different styles of leadership for different problems. Findings: The paper will find that humans are inherently obedient and reluctant obedient, reluctant to challenge authority and introduces the concept of blind obedience into police leadership. A distinction will be drawn between commanding in critical situations, which are rare, and leading in routine situations; the paper will conclude that to lead the police service through the turbulent times ahead, police leaders must be on guard against blind obedience and create an environment where subordinates have a voice and will be heard. The paper also finds that "micro-management" from a remote location is ineffective and that staff must be afforded time and space to undertake tasks and that strategic leaders must allow their subordinates, at the tactical and operational levels, freedom to act with the overall strategy; the paper recommends leaders adopt a mission command approach. Originality/value: The paper will contribute to understanding how subordinates and leaders interact and will be of value to all who lead, particularly in structured organisations like the police, where rank plays a factor in establishing a strict hierarchy. It introduces the concept of blind obedience into police leadership and warns that police leaders, and indeed leaders in all hierarchal organisations, must be on constant guard against it.